ANALISIS KINERJA KEUANGAN DAN NILAI TUKAR TERHADAP HARGA SAHAM PERUSAHAAN TERINDEKS DI IDXHEALTH - Siswantini, Tri; Nabila, Chelsea; Resti, Anggi Angga; Nopiyanti, Anita (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
Stock prices in the financial sector are a reflection of the company’s performance fundamentals. This quantitative research was conducted with the aim of analyzing financial performance, namely Profitability, Solvency, and Liquidity, as well as the Exchange Rate to Stock Price. The object used in this study is companies engaged in the health sector indexed in IDXHEALTH for the period 2019 – 2022. The sample determination method used purposive sampling and obtained 12 company samples with an observation period of 4 years. The hypothesis in this study was tested with a significance level of 5% (0.05) using Panel Data Regression Analysis and the E-views 12 program. The results found in this study are that Liquidity has no effect on Stock Price, Solvency has no effect on Stock Price, Profitability has no effect on Stock Price, and Exchange Rate has no effect on Stock Price